Utilizing the WTO-TRIPS flexibilities on public health at a regional level : a critical review of the East African Community framework - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2026)
Dissertation (LLM (Human Rights))--University of Pretoria, 2014.